Rhythm-Speech Correlations in a Corpus of Senegalese Drum Language - Ros, Sofiya (Frontiers in Communication, 2021)
In some African cultures, drumming is used for expressing linguistic meanings. Our research focuses on Senegalese musical traditions of encoding linguistic messages on the sabar drums. Senegalese drummers have the practice of playing drums in correlation to speech. We consider such rhythms and their linguistic correlates as being part of a Sabar drum language. The long-term goal of this investigation is to establish the linguistic properties of the Sabar drum language. To this end, this work relies on two kinds of research materials collected from Senegalese drummers: bàkks (classical Sabar phrases, not improvised on the spot) and Sabar improvisations including their translation to Wolof. We study the regularities between Wolof units and Sabar rhythms in the collected data. We tested the hypothesis of a syllable-level correspondence between Sabar and Wolof, assuming that each Sabar stroke represents a syllable or a number of syllables in Wolof. The analysis has shown that different drum strokes are more commonly associated with different types of vowels (front/central/back, open/close mid, close). These results reveal syllable-level regularities in the data.